Ð’Ð²ÐµÐ´ÐµÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ â€“ Ð¿ÐµÑ€ÑÐ¿ÐµÐºÑ‚Ð¸Ð²Ð½Ñ‹Ð¹ Ð¿ÑƒÑ‚ÑŒ Ð²Ð¾ÑÑÑ‚Ð°Ð½Ð¾Ð²Ð»ÐµÐ½Ð¸Ñ Ð¼ÑƒÐ¶ÑÐºÐ¾Ð¹ Ñ„ÐµÑ€Ñ‚Ð¸Ð»ÑŒÐ½Ð¾ÑÑ‚Ð¸ - Gibner, S. M.; Sudarikov, I. V.; Miroshnikov, Ya. O. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
There was examined an efficiency of cryopreserved placenta implantation under scrotum skin in 15 persons with sterility ofcombined genesis. Pregnancy in sterile couple is observed in 3 cases. Significant spermatogenesis improvement was noticed among 9 out of 11 patients subjected to the control examination. The most significant changes of spermatogenesis took place in a subgroup of males with an expressed secretory of sterility (concentration less 20 mln /ml, 7 patients). This subgroup is marked for the average thrice-repeated increase of spermatozoa concentration (р<0,001) and reliable improvement of principal qualitative spermatozoa indices: motility, percent of necro- and teratospermia (р<0,05). We consider the cryopreserved placenta implantation for spermatogenesis stimulation to be the most pertinent during secretory types of sterility; the pertinence of using cryopreserved placenta for improving qualitative spermatogenesis indices under normal spermatozoa concentration appears to be dubious, so this issue demandsthorough research. The suggested method of implantation into the scrotum does not yield traditional methods of implantation. No complications after its applicaton are observed.